A SWAT modeling approach to assess the impact of climate change on consumptive water use in Lower Chenab Canal area of Indus basin - Awan, Usman K.; Liaqat, Umar Waqas; Choi, Minha; Ismaeel, Ali (IWA Publishing, 2016)
Accurate assessment of spatio-temporal variations of consumptive water use (CWU) in large irrigation schemes is crucial for several hydrological applications. This study is designed to evaluate the impact of climate change on CWU in the Lower Chenab Canal (LCC) irrigation scheme of the Indus basin irrigation system of Pakistan. A distributed hydrological model, the soil and water assessment tool (SWAT), was spatially calibrated (2005–2009) and validated (2010–2012) for monthly CWU. The estimated CWU using the SWAT model showed promising results (the coefficient of determination (R2) = 0.87 ± 0.06, Nash–Sutcliffe model efficiency (NSE) = 0.83 ± 0.06)) when compared with CWU determined by the Surface Energy Balance Algorithm (SEBAL) (R2 = 0.87 ± 0.06, NSE = 0.83 ± 0.06). Future evaluation, performed by considering the representative concentration pathways (RCP) 4.5 and 8.5 climate change scenarios, showed that changes in temperature and rainfall would significantly influence the CWU in the LCC scheme. Compared with the reference period, annual water consumption in the basin would increase overall by 7% and 11% at the end of 2020 with monthly variations of –40% to 60% and –17% to 80% under RCP 4.5 and RCP 8.5 climate change scenarios, respectively. The water managers in the region have to consider this fluctuating consumptive use in water allocation plans due to climate change for better management of available water resources.